2017
DOI: 10.1158/0008-5472.can-17-1411
|View full text |Cite
|
Sign up to set email alerts
|

FSTL1 Promotes Metastasis and Chemoresistance in Esophageal Squamous Cell Carcinoma through NFκB–BMP Signaling Cross-talk

Abstract: Esophageal squamous cell carcinoma (ESCC) has a generally poor prognosis, and molecular markers to improve early detection and predict outcomes are greatly needed. Here, we report that the BMP-binding follistatin-like protein FSTL1 is overexpressed in ESCCs, where it correlates with poor overall survival. Genetic amplification of FSTL1 or chromosome 3q, where it is located, occurred frequently in ESCC, where FSTL1 copy number correlated positively with higher FSTL1 protein expression. Elevating FSTL1 levels by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 47 publications
5
42
0
Order By: Relevance
“…Compared with the empty vector controls, 119 genes were up‐regulated and 53 down‐regulated in the samples overexpressing AL121899.1 (Table , Figure B). Overexpressing AL121899.1 did not affect the expression of genes in the core module, but instead regulated a set of genes enriched on hallmark epithelial‐mesenchymal transition and other 19 immunologic or oncogenic signatures in MSigDB v6.2 (Table ), and also many genes that have been reported to be associated with prognosis, metastasis, chemoresistance or radioresistance of ESCC, such as SPARC, FSTL1, MUC4, DHCR7, LOX and CXCL1 . In addition, the up‐regulated genes were enriched on biological processes associated with regulation of insulin‐like growth factor transport and uptake ( P = 1.43 × 10 −6 ), post‐translational protein phosphorylation ( P = 8.70 × 10 −6 ), steroid metabolic process ( P = 1.32 × 10 −5 ) and digestion ( P = 3.09 × 10 −3 ) (Figure C, Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the empty vector controls, 119 genes were up‐regulated and 53 down‐regulated in the samples overexpressing AL121899.1 (Table , Figure B). Overexpressing AL121899.1 did not affect the expression of genes in the core module, but instead regulated a set of genes enriched on hallmark epithelial‐mesenchymal transition and other 19 immunologic or oncogenic signatures in MSigDB v6.2 (Table ), and also many genes that have been reported to be associated with prognosis, metastasis, chemoresistance or radioresistance of ESCC, such as SPARC, FSTL1, MUC4, DHCR7, LOX and CXCL1 . In addition, the up‐regulated genes were enriched on biological processes associated with regulation of insulin‐like growth factor transport and uptake ( P = 1.43 × 10 −6 ), post‐translational protein phosphorylation ( P = 8.70 × 10 −6 ), steroid metabolic process ( P = 1.32 × 10 −5 ) and digestion ( P = 3.09 × 10 −3 ) (Figure C, Table ).…”
Section: Resultsmentioning
confidence: 99%
“…These proteins have been linked to cancer progression, resistance to chemo-and radiotherapy, poor prognosis and/or metastasis [4,[44][45][46][47][48][49][50][51]. Therefore, targeting these proteins with JQ1 could be of clinical interest in TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…36 Previous studies showed that FSTL1 stimulates NF-κB signalling. 37,38 F I G U R E 3 Effects of FSTL1 on MMP-1, MMP-3, MMP-13, iNOS and COX-2 protein expression. Each column represents the mean ± SD.…”
Section: Discussionmentioning
confidence: 99%